Proton Therapy: Ever Shifting Sands and the Opportunities and Obligations within - Hill-Kayser, Christine E.; Both, Stefan; Tochner, zelig (Frontiers in Oncology, 2011)
Proton therapy is associated with significant benefit in terms of normal tissue sparing and potential radiation dose escalation for many patients with malignant diseases. Due to recognition of these qualities, the availability of this technology is increasing rapidly, both through increased availability of large centers, and with the possibility of smaller, lower cost proton therapy centers. Such expansion is associated with increased opportunity to provide this beneficial technology to larger numbers of patients; however, the importance of careful treatment planning and delivery, deliberate patient selection, rigorous scientific investigation including comparison to other technologies when possible, and mindfulness of ethical issues and cost effectiveness must not be forgotten. The obligation to move forward responsibly rests on the shoulders of radiation oncologists around the world. In this article, we discuss current use of proton therapy worldwide, as well as many of the factors that must be taken into account during rapid expansion of this exciting technology.